2022
DOI: 10.1001/jamanetworkopen.2022.14885
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Patient-Reported Outcome Measures for Maternal Postpartum Depression Using the Consensus-Based Standards for the Selection of Health Measurement Instruments Guideline

Abstract: IMPORTANCE Maternal depression is frequently reported in the postpartum period, with an estimated prevalence of approximately 15% during the first postpartum year. Despite the high prevalence of postpartum depression, there is no consensus regarding which patient-reported outcome measure (PROM) should be used to screen for this complex, multidimensional construct. OBJECTIVETo evaluate psychometric measurement properties of existing PROMs of maternal postpartum depression using the Consensus-Based Standards for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…In the Original Investigation titled “Assessment of Patient-Reported Outcome Measures for Maternal Postpartum Depression Using the Consensus-Based Standards for the Selection of Health Measurement Instruments Guideline: A Systematic Review,” published June 24, 2022, the affiliation for Rania Elkhateb was changed from Library to Department of Anesthesiology at the University of Arkansas for Medical Sciences, Little Rock. This article has been corrected …”
supporting
confidence: 67%
“…In the Original Investigation titled “Assessment of Patient-Reported Outcome Measures for Maternal Postpartum Depression Using the Consensus-Based Standards for the Selection of Health Measurement Instruments Guideline: A Systematic Review,” published June 24, 2022, the affiliation for Rania Elkhateb was changed from Library to Department of Anesthesiology at the University of Arkansas for Medical Sciences, Little Rock. This article has been corrected …”
supporting
confidence: 67%
“…Validation ongoing in translated versions and diverse populations. 24 h postpartum (ObsQoR-10 validated for up to 72 h postpartum) Outpatient Global World Health Organization Quality of Life–BREF (WHO-QOLBREF) 56 No 6 wk postpartum Pain Brief Pain Inventory-Short Form (BPI-SF) 58 No The only PROM with adequate content validity and internal consistency (low-quality evidence) Psychosocial distress Edinburgh Postnatal Depression Scale (EPDS) 59 Yes Sufficient content validity, with moderate evidence for sufficient internal consistency, which was not observed in other PROMs Anxiety: State-Trait Anxiety Inventory (STAI) No Registered with PROSPERO 2021 CRD42021260004 Available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021260004 Sleep Bergen Insomnia Scale (BIS) 60 No Does not assess several important domains of sleep, eg, sleep duration (and efficiency), chronotype, sleep-disordered breathing, and medication use Fatigue Fatigue Assessment Scale 61 No The only PROM with adequate content validity and internal consistency Motherhood experience Postpartum bonding Questionnaire 62 Yes The only PROM with sufficient structural validity, internal consistency, and reliability PROM , patient-reported outcome measure. …”
Section: Introductionmentioning
confidence: 99%
“…The 2 newly published studies, Smythe et al and Sultan et al, are systematic reviews (Smythe et al also comprises a meta-analysis) dealing with the topic of perinatal mental health (ie, mental health during the time of pregnancy up to 1 year after birth). Smythe et al estimated prevalence rates of perinatal depression and anxiety in parental dyads and associated factors.…”
mentioning
confidence: 99%
“…Given the paucity of dyadic studies, no prevalence estimate for anxiety could be determined. Sultan et al examined the psychometric properties of 10 existing patient-reported outcome measures for assessing maternal postpartum depression. Although all included patient-reported outcome measures demonstrated adequate content validity, only the Edinburgh Postnatal Depression Scale received a class A recommendation (recommended for use).…”
mentioning
confidence: 99%
See 1 more Smart Citation